More Pitfalls in Demand and Supply Curve Analysis - Frisch, Ragnar (Quarterly Journal of Economics, 1934)
Journal Article More Pitfalls in Demand and Supply Curve Analysis Get access Ragnar Frisch Ragnar Frisch University of Norway Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 48, Issue 4, August 1934, Pages 749–755, https://doi.org/10.2307/1883550 Published: 01 August 1934